Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian Di Apotek “X” Cilangkap Jakarta Timur Periode April - Mei 2025 - Retno Fitriati; Thassya Nur Utami (Journal of Pharmacy and Clinical Practice, 2026)
Service and satisfaction are interrelated aspects. Satisfaction allows all parties to evaluate the quality of services provided, whether they have improved or deteriorated. The purpose of this study was to assess patient satisfaction with pharmaceutical services at Pharmacy "X" Cilangkap, East Jakarta. This study used a quantitative observational method with a cross-sectional approach. Data collection was conducted using questionnaires distributed to patients purchasing medications at Pharmacy "X" Cilangkap, East Jakarta. The population in this study was 9,860, and using the Slovin formula, a sample of 385 was obtained. This was a quantitative observational study using a cross-sectional method. The results of the study showed that patient satisfaction at Pharmacy "X" Cilangkap, East Jakarta was highest in the drug information service category, with 63.9%. Job characteristics were significantly associated with satisfaction with drug information services. Meanwhile, gender, age, and education were not significantly associated. The conclusion of this study is that the level of satisfaction of pharmaceutical services in patients at Pharmacy "X" Cilangkap East Jakarta based on 5 dimensions of pharmaceutical services is in the category of pharmacy appearance as many as 221 people (57.4%) respondents felt very satisfied, friendliness of officers as many as 218 people (56.6%) respondents felt very satisfied, drug information services as many as 246 people (63.9%) respondents felt very satisfied, drug availability as many as 199 people (51.6%) respondents felt very satisfied, and speed of service as many as 245 people (63.6%) respondents felt very satisfied. Keywords: Satisfaction, Pharmaceutical Services, Pharmacy